THE RELATIONSHIP OF BLENDED LEARNING IN THE NEW NORMAL PERIOD ON STUDENT LEARNING OUTCOMES - Suci Elvina (Adisam Publisher, 2023)
After implementing Circular Letter Number 4 of 2020 concerning the Implementation of Education during the Coronavirus Dieses (Covid-19) Emergency, the term New Normal emerged in social life during the pandemic. After the policy was born, the use of Blended Learning learning was rife as a solution to the existing situation. Blended Learning learning system that combines online and offline learning. The aim of this research is to analyze the impact of blended learning during the new normal period on students' practical learning outcomes and what learning outcomes are obtained by class X students at UNP Laboratory Development High School. A total of 152 students were the research sample. This research method was quantitative with an ex-post facto research type and a correlational research design. The results of this research show that there is a relationship between blended learning and practical learning outcomes in craft and entrepreneurship subjects at UNP Laboratory Development High School.